A novel multilateral teleoperation scheme with power-based time-domain passivity control. (July 2018) - Chen, Zheng; Pan, Ya-Jun; Gu, Jason; Forbrigger, Shane
Multilateral teleoperation systems, which are extended from the traditional bilateral teleoperation, have become subject to increasing attention in current years, with increasing industrial requirements, such as the remote operation of larger objects and more complex tasks. In this paper, a general multilateral teleoperation control problem is discussed, in which n masters remotely control n slaves through delayed communication channels. A novel communication structure is proposed to satisfy the multiple master–slave communication requirement, in which weighting coefficients are chosen freely to perform the weighted effects of different masters or slaves. Power-based time-domain passivity control is subsequently developed for the complex multiple master–slave communication channel, to achieve the passivity of multilateral teleoperation systems under time delay. Experiments on a teleoperation system with two masters and two slaves are described; the results verify the effectiveness of the proposed control scheme.